Anxiety: analysis of impacts on quality of life and therapeutic approaches, an integrative review (Research, Society and Development, 2020)
Objective: to describe the consequences that anxiety triggers and the therapeutic resources available. Methods: It consists of an Integrative Literature Review made from articles available in the Virtual Health Library (VHL). The final sample obtained a total of 09 articles. Result: It was possible to identify several situations in which anxiety is prevalent, as well as the damage it causes in people's lives, and even though it needs improvement, the health care sectors need to be able to provide assistance in a trained, humanized manner in the in order to offer a better quality of life. Final Considerations: Anxiety must be identified as early as possible to minimize the consequences, making it necessary to make appropriate use of therapeutic resources and to train the team so that the assistance is effective for the benefit of the patient, as the health team assumes a crucial role the care to be taken in order to promote better coping.